Complement-activating donor-specific anti-HLA antibodies and solid organ transplant survival: a systematic review and meta-analysis - Bouquegneau, Antoine; Süsal, Caner (PLoS medicine, 2018)
Background Anti-human leukocyte antigen donor-specific antibodies (anti-HLA DSAs) are recognized as a major barrier to patients’ access to organ transplantation and the major cause of graft failure. The capacity of circulating anti-HLA DSAs to activate complement has been suggested as a potential biomarker for optimizing graft allocation and improving the rate of successful transplantations. Methods and findings To address the clinical relevance of complement-activating anti-HLA DSAs across all solid organ transplant patients, we performed a meta-analysis of their association with transplant outcome through a systematic review, from inception to January 31, 2018. The primary outcome was allograft loss, and the secondary outcome was allograft rejection. A comprehensive search strategy was conducted through several databases (Medline, Embase, Cochrane, and Scopus). A total of 5,861 eligible citations were identified. A total of 37 studies were included in the meta-analysis. Studies reported on 7,936 patients, including kidney (n = 5,991), liver (n = 1,459), heart (n = 370), and lung recipients (n = 116). Solid organ transplant recipients with circulating complement-activating anti-HLA DSAs experienced an increased risk of allograft loss (pooled HR 3.09; 95% CI 2.55–3.74, P = 0.001; I2 = 29.3%), and allograft rejection (pooled HR 3.75; 95% CI: 2.05–6.87, P = 0.001; I2 = 69.8%) compared to patients without complement-activating anti-HLA DSAs. The association between circulating complement-activating anti-HLA DSAs and allograft failure was consistent across all subgroups and sensitivity analyses. Limitations of the study are the observational and retrospective design of almost all included studies, the higher proportion of kidney recipients compared to other solid organ transplant recipients, and the inclusion of fewer studies investigating allograft rejection. Conclusions In this study, we found that circulating complement-activating anti-HLA DSAs had a significant deleterious impact on solid organ transplant survival and risk of rejection. The detection of complement-activating anti-HLA DSAs may add value at an individual patient level for noninvasive biomarker-guided risk stratification. Trial registration National Clinical Trial protocol ID: NCT03438058.
Gesehen am 04.07.2019